INTERROGATING GENDER PREFERENCE AND ITSIMPLICATIONS ON THE MENTAL HEALTH OF WOMEN ANDGIRL CHILDREN IN NIGERIA (IUS LAW Journal, 2025)
Premium desire and attention is placed on male children in Nigeria; this being the patriarchal and socio-cultural inter-generational heritage. Through the growth and socialization process, the girl-child is treated inferiorly and made to believe less in her worth and abilities. From early childhood, it is ingrained in her that she always comes after the boy-child. The society also places loud demands on women to produce male children before they can be reckoned with in marriage hence, women risk health, personal growth and wellbeing to satisfy this societal craving. The girl-child inputs twice effort and work as the male child to produce the same or less result as her male counterpart whom society has naturally put on a higher pedestal. Adopting the doctrinal method, this paper examines the impact the pressure of these demands has produced in the mental well-being of women and girl-children. It found that over time, women and girl-children have developed anxiety, fear, frustration, and other harmful social behavior with resultant spiral negative effects including but not limited to depression, suicide and other mental health challenges. The paper contends that since the accomplishment of any individual stems from her/his mental well-being, this narrative must change. It concludes that gender should not be the bases for human value; life should reward everyone according to inputs and not gender; society should evolve to the extent that lineage continuity can be both matriarchal and patriarchal.
Keywords: Gender Mental health Nigeria